2019
DOI: 10.3390/su11071880
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Farm-scale Multitrophic Recirculating Aquaculture System with the Addition of Rhodovulum sulfidophilum for Milkfish (Chanos chanos) Coastal Aquaculture

Abstract: Globally, coastal aquaculture is growing due to the large demand for marine products. Specific impacts caused by coastal aquaculture on the environment include the discharge of culture farm effluents, stress on ground water (the absence of recycling), nutrient pollution, and diseases of cultured animals. Three methods, integrated multitrophic aquaculture (IMTA), recirculating aquaculture system (RAS), and beneficial bacteria for aquaculture, have been developed to solve these problems. In this study, the advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Therefore, the addition of anoxygenic phototrophic bacteria to water changes the microbial community structure and improves the water quality. Anoxygenic phototrophic bacteria are also frequently used as beneficial bacteria for aquaculture [53,54]. Therefore, a decrease in anoxygenic phototrophic bacteria after the addition of MG is harmful for DOM recycling and water quality in small MCPs (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the addition of anoxygenic phototrophic bacteria to water changes the microbial community structure and improves the water quality. Anoxygenic phototrophic bacteria are also frequently used as beneficial bacteria for aquaculture [53,54]. Therefore, a decrease in anoxygenic phototrophic bacteria after the addition of MG is harmful for DOM recycling and water quality in small MCPs (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the integration of a recirculating water system (RAS) for fish production, with other crops as sea urchin and seaweed, was efficient to maintain water quality and to reduce the waste load to the environment. The association of these two aquaculture production systems, RAS and IMTA, is relatively new, but has several advantages, allowing a tight control and monitoring of water quality, as recently demonstrated by Chang et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The integration of multiple species from different trophic levels in the same IMTA design allows to recover particulate and dissolved nutrients in the form of valuable biomass of these extra crops. This has been previously described in studies addressing the combined use of bivalves and seaweeds [14][15][16][17][18][19][20][21][22][23] , bivalves and microalgae 24 , bivalves and halophytes 25 , echinoderms and seaweeds 26 , polychaetes and seaweeds 27 and polychaetes and halophytes 11 . More than 50% of these studies were performed in the time-period between 2015 and 2020 evidencing that this is currently a hot-topic in aquaculture.…”
mentioning
confidence: 82%